DROUGHT LIMITS INDUCED TWINING BY LEAF DAMAGE IN THE CLIMBING PLANT IPOMOEA PURPUREA (L.) ROTH (CONVOLVULACEAE) LA SEQUIA LIMITA LA INDUCCIÓN DE TREPADO POR DAÑO FOLIAR EN LA PLANTA TREPADORA IPOMOEA PURPUREA (L.) ROTH (CONVOLVULACEAE) - Cristian Atala (Universidad de Concepción, 2009)
The environment may limit the expression of induced responses to herbivory, such as increased chemical or physical defenses. Recent studies in climbing plants have shown that leaf damage induces twining. This response may confer protection against ground herbivores in the field. We addressed the effect of drought on the induced twining of the annual vine Ipomoea purpurea (Convolvulaceae), which can experience drought stress in natural conditions. In a greenhouse experiment, we recorded twining rate (proportion of plants successfully climbing at a given time) of damaged and undamaged individuals of I. purpurea subjected to control watering and water shortage treatments. We also estimated stem growth rate and stem water content in experimental plants, just after the evaluation of climbing success. Plants in the drought treatment showed reduced twining induction by leaf damage compared to control plants. Neither stem growth nor stem water content were affected by leaf damage or drought. Results suggest that drought constrains the induced twining through mechanisms not directly related to stem growth and water content. It is suggested that drought might trigger signals that counteract those elicited by leaf damage. The induced twining may be an advantage in the presence of ground herbivores, but the environmental susceptibility of this response may limit its ecological significance. El ambiente puede limitar la expresión de las respuestas inducidas por la herbivoría, como el aumento en las defensas químicas o físicas. Estudios recientes en plantas trepadoras muestran que el daño foliar induce el trepado. Esta respuesta podría conferir protección contra herbívoros en terreno. En este estudio investigamos el efecto de la sequía sobre la inducción de trepado en la trepadora anual Ipomoea purpurea (Convolvulaceae), planta que en condiciones naturales puede experimentar estrés por sequía. En un experimento de invernadero, se registró la tasa de enredo (proporción de plantas que se enredan exitosamente en un tiempo dado) de plantas dañadas y no dañadas de I purpurea, expuestas a tratamientos de riego control y sequía. También se estimó la tasa de crecimiento y el contenido hídrico del tallo, justo después de la evaluación del trepado. Las plantas en el tratamiento de sequía mostraron una reducción en la inducción de trepado por daño foliar comparado con plantas control. Ni la tasa de crecimiento ni el contenido hídrico se afectaron por el daño foliar o la sequía. Los resultados sugieren que la sequía limita la inducción de trepado por medio de mecanismos no directamente relacionados con el crecimiento y el contenido hídrico del tallo. Se sugiere que la sequía podría inducir señales que se contraponen con las generadas por el daño foliar. La inducción de trepado puede ser una ventaja en la presencia de herbívoros rastreros, pero la susceptibilidad ambiental de esta respuesta puede limitar su relevancia ecológica.